2023
DOI: 10.1111/clr.14028
|View full text |Cite
|
Sign up to set email alerts
|

Osteoinductive calcium phosphate with submicron topography as bone graft substitute for maxillary sinus floor augmentation: A translational study

Abstract: Objectives The aim of this study was the preclinical and clinical evaluation of osteoinductive calcium phosphate with submicron surface topography as a bone graft substitute for maxillary sinus floor augmentation (MSFA). Material and Methods A preclinical sheep model of MSFA was used to compare a calcium phosphate with submicron needle‐shaped topography (BCPN, MagnetOs Granules, Kuros Biosciences BV) to a calcium phosphate with submicron grain‐shaped topography (BCPG) and autologous bone graft (ABG) as control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…, angiogenesis), and the growth of bones. 44,45 This is possibly attributed to the porosity in the hybrid-pore (CMS) 1.5 (CS) 1.5 and submicron-pore (CMS) 1.5 (CS) 1.5 substitutes, which are 82.85% and 71.38%, respectively, as shown in Table S2 (ESI†). The higher porosity in the bone graft allows more cells or blood vessels to penetrate into the empty area for bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, angiogenesis), and the growth of bones. 44,45 This is possibly attributed to the porosity in the hybrid-pore (CMS) 1.5 (CS) 1.5 and submicron-pore (CMS) 1.5 (CS) 1.5 substitutes, which are 82.85% and 71.38%, respectively, as shown in Table S2 (ESI†). The higher porosity in the bone graft allows more cells or blood vessels to penetrate into the empty area for bone regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…To enhance the osteoinductive properties of the bone graft, some research demonstrated a significant influence of the surface structure of the bone grafts to the behavior of macrophages (i.e., a type of immune cell), the formation of blood vessels (i.e., angiogenesis), and the growth of bones. 44,45 This is possibly attributed to the porosity in the hybrid-pore (CMS) 1.5 (CS) 1.5 and submicron-pore (CMS) 1.5 (CS) 1.5 substitutes, which are 82.85% and 71.38%, respectively, as shown in Table S2 (ESI †). The higher porosity in the bone graft allows more cells or blood vessels to penetrate into the empty area for bone regeneration.…”
Section: Composite Bone Graftsmentioning
confidence: 99%
“…The superior osteoinductivity of autografts is associated with specialized bone cells, growth factors, and a functional vascular network they contain. Tailoring physicochemical properties of CaPs, such as chemical composition, surface topography and microstructure, was shown to be effective in engineering CaPs with advanced osteoinductivity and bone-forming ability ( Davison et al, 2014 ; Tang et al, 2018 ; van Dijk et al, 2023a ; van Dijk et al, 2023b ). This requires investigating a large design space to find the synthesis and processing parameters that lead to CaPs with optimal physicochemical properties that in turn result in effective biomaterials-induced bone healing.…”
Section: Introductionmentioning
confidence: 99%